HUBUNGAN MEAL SKIPPING, KONSUMSI CAMILAN DAN AKTIVITAS FISIK DENGAN STATUS GIZI LEBIH PADA REMAJA DI SMAS IT NURURRAHMAN DEPOK - Nabila Tsurayya (2022)
The process of growth and development experienced by adolescents triggers behavioral changes that can lead to healthy and unhealthy eating behavior. Unhealthy eating behavior can lead to nutritional problems such as being overweight. One example of unhealthy eating behavior in adolescents is meal skipping and snack consumption. In addition, low physical activity also significantly influences the incidence of overweight. This study aims to determine the relationship between meal skipping, snack consumption, and physical activity with overweight adolescents at SMAS IT Nururrahman Depok. This type of research is analytic observational with a cross-sectional study. The population is 60 SMAS IT Nururrahman Depok students aged 15-17 years and taken using stratified random sampling. Data were collected using questionnaires and measuring instruments like digital scales and microtoise. Based on the research, 46.7% of respondents are overweight. The results of the bivariate test using chi-square showed that there was a relationship between snack consumption (p=0.010) and physical activity (p=0.044) with being overweight, while meal skipping did not show an association with being overweight (p=0.162). It can be concluded that there is a relationship between snack consumption and physical activity in overweight adolescents and there is no relationship between meal skipping and overweight adolescents. Keywords : Meal Skipping, Snack Consumption, Physical Activity, Overweight, Adolescents